MOTIVASI ORANGTUA MENYEKOLAHKAN ANAKNYA DI SEKOLAH DASAR ISLAM TERPADU SYIFA BUDI PEKANBARU - Ria Yuli Apriani; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at SDIT Al-Azhar Pekanbaru. The purpose of this study is to determine parents' satisfaction with education services at SDIT Al-Azhar Pekanbaru. The focus of this research is the factors that affect parents' satisfaction toward education service at SDIT Al-Azhar Pekanbaru. The technique of determining samples purposive sampling and set the number of samples as many as 10 people. The author uses qualitative descriptive method and Instrument data is observation, interview. The study found that parents' satisfaction with education service by Al-Azhar Syifa Budi Pekanbaru IT Elementary School can be seen from several points as follows: Parents satisfaction on educators, it is known that all research informants are very satisfied with the quality of educators in IT Elementary School AL Azhar Syifa Budi Pekanbaru. Parents Satisfaction with Facilities, Infrastructure and Management it is known that the informants are very satisfied with the availability of facilities, infrastructure and policies of the management of SD IT Al Azhar Syifa Budi Pekanbaru. Parents Satisfaction Against Content Standards, Processes and Assessment, According to the informant's acknowledgment, students are not only skilled in the lesson but also very controlled in how to behave. According to this informant is a very good achievement considering the challenges of the times that must be faced by their child science is not enough, need a strong character to face social changes for the future. Keywords: Rational Choice, Child Education